2018
DOI: 10.1101/271197
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Top-down inputs drive neuronal network rewiring and context-enhanced sensory processing in olfaction

Abstract: Much of the computational power of the mammalian brain arises from its extensive top-down projections. To enable neuron-specific information processing these projections have to be precisely targeted. How such a specific connectivity emerges and what functions it supports is still poorly understood. We addressed these questions in silico in the context of the profound structural plasticity of the olfactory system. At the core of this plasticity are the granule cells of the olfactory bulb, which integrate botto… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 60 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…Context profoundly shapes odor perception [16, 17, 22, 44, 92, 100], and previous studies have demonstrated the critical role of cortical feedback to the OB in the formation of odor-context associations [47, 56]. Cortical feedback can also enhance odor discrimination [2, 21, 52, 57, 68] and generalization [49]. Some studies have implicated feedback in the generation of beta oscillations, thought to be associated with olfactory learning [42, 43, 59, 60, 65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Context profoundly shapes odor perception [16, 17, 22, 44, 92, 100], and previous studies have demonstrated the critical role of cortical feedback to the OB in the formation of odor-context associations [47, 56]. Cortical feedback can also enhance odor discrimination [2, 21, 52, 57, 68] and generalization [49]. Some studies have implicated feedback in the generation of beta oscillations, thought to be associated with olfactory learning [42, 43, 59, 60, 65].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical and computational studies have also explored possible mechanisms by which feedback may impose these effects. Models of top-down, direct cortical feedback to the bulb which include plasticity in the feedback and in cortex have been able to reproduce odor association with visual context [56] and differences in cortical reorganization during passive vs. active learning [100]; demonstrate adaptation to specific olfactory environments and odor tasks when guided by neurogenesis [2]; and explain differential responses to the same odor under different contexts [49]. Other models have demonstrated further effects of neuromodulation on OB activity, such as normalization of output neuron response [52], increasing spike synchrony [20, 50], and general enhancement of odor discrimination [51, 52].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our results suggest that a primary determinant of the effect of cortical feedback on the bulb output is the network architecture of GCs, as opposed to which of these cells are specifically targeted. This implies that theories of feedback and neurogenesis in the bulb that rely on specific targeting of GCs and MCs [12,28,93] may require additional components beyond the basic MC-GC network to be feasible.…”
Section: Network Architecture Shapes Cortical Feedbackmentioning
confidence: 99%
“…However, the sheer number of neurons, encompassing tens of thousands of excitatory cells and millions of inhibitory cells [1]; intricate network architecture [2][3][4]; and complex spiking dynamics [5][6][7][8][9] make detailed biophysical simulation impractical at large scale. Thus, many studies use random connections or simple distance-dependent functions to establish MC-GC connectivity [10][11][12][13][14][15][16][17][18][19][20][21][22] and often study smaller networks on the order of hundreds or even tens of neurons [10,11,13,14,19,[22][23][24], allowing for highly complex, conductance-based neuronal frameworks [7]. Other approaches use rate-based or population equations [12,21,25] thereby facilitating models with larger numbers of neurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation